Selectivity of Enzymatic Conversion of Oligonucleotide Probes during Nucleotide Polymorphism Analysis of DNA - Vinogradova, O.A. (A.I. Gordeyev, 2010)
The analysis of DNA nucleotide polymorphisms is one of the main goals of DNA diagnostics. DNA–dependent enzymes (DNA polymerases and DNA ligases) are widely used to enhance the sensitivity and reliability of systems intended for the detection of point mutations in genetic material. In this article, we have summarized the data on the selectiveness of DNA–dependent enzymes and on the structural factors in enzymes and DNA which influence the effectiveness of mismatch discrimination during enzymatic conversion of oligonucleotide probes on a DNA template. The data presented characterize the sensitivity of a series of DNA–dependent enzymes that are widely used in the detection of noncomplementary base pairs in nucleic acid substrate complexes. We have analyzed the spatial properties of the enzyme–substrate complexes. These properties are vital for the enzymatic reaction and the recognition of perfect DNA–substrates. We also discuss relevant approaches to increasing the selectivity of enzyme–dependent reactions. These approaches involve the use of modified oligonucleotide probes which “disturb” the native structure of the DNA–substrate complexes.